Effects of promoting increased duration and exclusivity of breastfeeding on adiposity and insulin-like growth factor-I at age 11.5 years: a randomized trial - Martin, Richard M (2013)
IMPORTANCE: Evidence that increased duration and exclusivity of breastfeeding reduces child obesity risk is based on observational studies that are prone to confounding. OBJECTIVE: To investigate effects of an intervention to promote increased duration and exclusivity of breastfeeding on child adiposity and circulating insulin-like growth factor (IGF)-I (which regulates growth). DESIGN: Cluster-randomized controlled trial. SETTING: 31 Belarusian maternity hospitals and their affiliated polyclinics, randomized to usual practices (n=15) or a breastfeeding promotion intervention (n=16). PARTICIPANTS: 17,046 breastfeeding mother-infant pairs enrolled in 1996/7, of whom 13,879 (81.4%) were followed-up between January 2008 and December 2010 at a median age of 11.5 years. INTERVENTION: Breastfeeding promotion intervention modeled on the WHO/UNICEF Baby Friendly Hospital Initiative. MAIN OUTCOME MEASURES: Body mass index (BMI), fat and fat-free mass indices (FMI and FFMI), percent body fat, waist circumference, triceps and subscapular skinfold thicknesses, overweight and obesity, and whole-blood IGF-I. Primary analysis was based on modified intention-to-treat (without imputation), accounting for clustering within hospitals/clinics. RESULTS: The experimental intervention substantially increased breastfeeding duration and exclusivity (43% vs. 6% and 7.9% vs. 0.6% exclusively breastfed at 3 and 6 months, respectively) versus the control intervention. Cluster-adjusted mean differences in outcomes at 11.5 years between experimental vs. control groups were: 0.19 kg/m(2) (95% 4 CI: −0.09, 0.46) for BMI; 0.12 kg/m(2) (−0.03, 0.28) for FMI; 0.04 kg/m(2) (−0.11, 0.18) for FFMI; 0.47% (−0.11, 1.05) for % body fat; 0.30 cm (−1.41, 2.01) for waist circumference; −0.07 mm (−1.71, 1.57) for triceps and −0.02 mm (−0.79, 0.75) for subscapular skinfold thicknesses; and −0.02 standard deviations (−0.12, 0.08) for IGF-I. The cluster-adjusted odds ratio for overweight / obesity (BMI ≥85(th) percentile vs <85(th) percentile) was 1.18 (1.01, 1.39) and for obesity (BMI ≥95(th) vs <85(th) percentile) was 1.17 (0.97, 1.41). CONCLUSIONS AND RELEVANCE: Among healthy term infants in Belarus, an intervention that succeeded in improving the duration and exclusivity of breastfeeding did not prevent overweight or obesity, nor did it affect IGF-I levels, at age 11.5 years. Breastfeeding has many advantages, but population strategies to increase the duration and exclusivity of breastfeeding are unlikely to curb the obesity epidemic.